Can “Rover” help with mental health during the COVID-19 pandemic? Results from the Canadian Longitudinal Study on Aging (CLSA) - Falck, Ryan S.; Liu-Ambrose, Teresa; Noseworthy, Matthew; Kirkland, Susan; Griffith, Lauren E.; Basta, Nicole E.; McMillan, Jacqueline M.; Raina, Parminder (Frontiers in Psychiatry, 2022)
COVID-19 has negatively affected the mental health and well-being of adults, and thus it is important to examine potential factors which may influence mental health during the pandemic. We thus examined the association between pet ownership and depression/anxiety symptoms based on mental health disorder status during the COVID-19 pandemic. We included 12,068 cognitively healthy participants (45-86 years at study entry) from the Canadian Longitudinal Study on Aging (CLSA) Comprehensive cohort who completed the first follow-up ([FU1]; 2015-2018), and COVID-19 Survey entry (April-May 2020) and exit (September-December 2020). Participants self-reported at FU1 if they owned a pet (yes/no). Participants were dichotomized as with or without a mental health disorder based on self-reported diagnosis of depression, anxiety, or mood disorders at baseline assessment (2011-2015) or FU1. Depressive symptoms were indexed using the 10-item Center for Epidemiological Studies Depression Scale (CESD-10) at FU1, and COVID-19 entry/exit surveys. Anxiety symptoms were assessed using the General Anxiety Disorder Questionnaire (GAD-7) at COVID-19 entry/exit surveys. Final models adjusted for age, sex, body mass index, income, education, living status, smoking status, relationship status, and alcohol intake. Forty-percent of participants owned a pet at FU1. Among those without a mental health disorder, there were no significant differences in CESD-10 between participants who owned pets compared with those without pets. For people with a mental health disorder, pet owners had higher CESD-10 (estimated mean difference range: 0.56 – 1.02 points; p < 0.05) and GAD-7 scores (estimated mean difference range: 0.28 – 0.57 points; p < 0.05) at both COVID-19 Questionnaire Study entry and exit. Among people with mental health disorders, pet ownership was associated with poor mental health symptoms during April 2020 to December 2020 of the COVID-19 pandemic.